Pun and games : jokes, riddles, daffynitions, tairy fales, rhymes, and more wordplay for kids - Lederer, Richard, 1938-; Morice, Dave, 1946- (Chicago : Chicago Review Press, 1996)
An introduction to wordplay, including puns, spoonerisms, riddles, and more.
Kliatt, November 1996
Kliatt
5.5
5-8
5-8
Keywords: Puns and punning; Riddles, Juvenile; Word games; Puns and punning; Riddles; Word games; Puns; Riddles; Word games